THE IMPACT OF SLEEP ON COGNITIVE BRAIN FUNCTIONS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Sleep is not a passive state but an active physiological process that plays a decisive role in maintaining cognitive health. This article examines sleep phases, neurophysiological mechanisms, and the influence of sleep on attention, memory, learning, and decision-making. Special attention is given to the consequences of chronic sleep deprivation and sleep disorders. Neuroscientific data are presented, emphasizing the need for quality sleep to ensure effective mental performance. Keywords: sleep, cognitive functions, memory, attention, brain, sleep stages, sleep deprivation, neuroplasticity.